MARKETING STRATEGY OF RUP «BMZ» IN THE PERIOD OF WORLD FINANCIAL-ECONOMIC CRISIS - V. V. Zaitsev (Литьë и металлургия)
The marketing strategy of RUP «BMZ» in the period of worldwide financial-economic crisis is disclosed. It is shown that it is aimed at the maximum increase of export in all directions.